Development of a Style Guide for the Traffic Flow Management Traffic Situation Display Graphical User Interface. (September 2016) - Bastholm, Robert; Masalonis, Anthony; Yuditsky, Tanya
Traffic Flow Management (TFM) functions to minimize airspace congestion and maximize safety and efficiency. TFM personnel at the U.S. Federal Aviation Administration use Traffic Situation Display (TSD) software to observe air traffic and weather systems and issue strategic congestion-mitigation initiatives to Air Traffic Control facilities. Since its initial deployment, the TSD has been augmented by many groups of developers. This distributed process has led to an inconsistent interface that does not always adhere to best usability practices, especially because during the initial stages of development there was little human factors involvement. This can have a detrimental effect on new users learning the interface and also may make experienced users more likely to make errors. We developed a style guide for an operational Air Traffic Management tool, and a companion consistency assessment, to help developers (a) adhere to usability principles for future software expansions and (b) bring older portions of the interface into compliance with user-centered design. We discuss the process of style guide development—including the unique aspects of the TFM user population and application domain and their implications for creating a style guide for TFM software—and the applicability of our guide beyond the TSD tool.